Strategi Pengembangan Kurikulum 2013 Pendidikan Agama Islam Berbasis Multikultural - Triana Rosalina Noor; Khoirun Nisa'il Fitriyah (PALAPA, 2021)
Conflicts with ethnic and religious nuances is partly due to the lack of insight into the understanding of cultural diversity. Responding to this situation, Islamic Religious Education is important to develop the multicultural perspective so that the reality of a multicultural society can be accommodated in it. This study used a qualitative approach with the type of case study, with the research location at SMA Kertajaya Surabaya. The informants of this study were the principal and Islamic education teachers, using the method of collecting data through interviews, observation and documentation study. The data that has been obtained are analyzed, interpreted and interpreted qualitatively descriptive. The findings obtained that the formulation of the PAI curriculum that applied was flexible and based on an analysis of the situation faced by the community. The PAI design that is applied considers the multicultural aspects that exist in society by paying attention to the situation of students, and the teachers who carry out learning activities. The strategy used is to include multicultural values such as a sense of justice, love and compassion, mutual respect between teachers and students, between school institutions and elements to the society.